The Silent Board: How Language Diversity May Influence the Work Processes of Corporate Boards. (22nd October 2014) - Piekkari, Rebecca; Oxelheim, Lars; Randøy, Trond
Abstract Manuscript Type Empirical. Research Question/Issue Corporate boards often change their working language when they acquire foreign members. Consequently, boards "talk" in one language but "think" in another. The present study explores and explains how language diversity influences work processes of corporate boards. Research Findings/Insights On the basis of a multiple case study of nine multinational corporations (MNCs) from four Nordic countries, we discovered evidence of impoverished and silenced discussions in board meetings in those case companies that were unprepared to switch to English as the new working language of the board. Some board members found it difficult to contribute to board meetings and articulate disagreement. In contrast, such effects were not revealed in the well‐prepared companies. Overall, the presence of employee representatives on the boards made it more difficult to conduct work processes in English because these members often lacked sufficient language proficiency. Thus, our findings suggest that the board co‐determination act of the Nordic corporate governance model may be associated with the hidden costs of using a non‐native language. Theoretical/Academic Implications Our study makes four contributions to research on board diversity. Firstly, it highlights the "silencing effect" of language diversity on board processes. Secondly, it emphasizes the linkage between language diversity and board processes. Thirdly, it provides additional evidence that language is a distinct dimension of diversity. Fourthly, it discovers language in board work as a new research topic that is worthy of scholarly attention. Practitioner/Policy Implications Firms need to anticipate the potential effects of language diversity on the work processes of their boards in order to ensure that "the voice of diversity" is heard. The board itself as well as the rest of the organization can take preparatory measures such as producing all board material in the new working language and selecting board members with the required language proficiency. Although these measures can be implemented gradually or at a faster pace, they need to be in place before foreign members join the board. Consistent use of one and the same language in the corporate board and the executive management team supports transparency and good corporate governance practices. In our opinion, reaping the benefits of board diversity is the particular responsibility of the chairperson. Even though English is generally well understood in the Nordic countries, chairpersons should also consider the possible negative effects associated with the use of a board language that is non‐native to most of its members.